2017
DOI: 10.1002/ajp.22711
|View full text |Cite
|
Sign up to set email alerts
|

Social interactions and activity patterns of old Barbary macaques: Further insights into the foundations of social selectivity

Abstract: Human aging is accompanied by a decrease in social activity and a narrowing in social networks. Studies in nonhuman primates may provide valuable comparative insights in which way aging impacts social life, in the absence of cultural conventions and an awareness of a limited lifetime. For female Barbary macaques at "La Forêt des Singes" in Rocamadour, France, we previously reported an age-associated decrease in active grooming time and network size. Here, we aimed to extend these findings by investigating in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 61 publications
6
40
0
Order By: Relevance
“…Changes in activity patterns with increasing age might add to the decrease in motivation to participate and persist. Considering the time spent on highly energetic activities like running, climbing and jumping, a study on Barbary macaques found an age-related decline, suggesting that older monkeys were less physically able or less motivated to engage in such activities [30]. The exploration of the tasks in our study also required physical engagement to obtain the reward.…”
Section: Discussionmentioning
confidence: 90%
“…Changes in activity patterns with increasing age might add to the decrease in motivation to participate and persist. Considering the time spent on highly energetic activities like running, climbing and jumping, a study on Barbary macaques found an age-related decline, suggesting that older monkeys were less physically able or less motivated to engage in such activities [30]. The exploration of the tasks in our study also required physical engagement to obtain the reward.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, behavioral studies in rodents have also shown a decrease in social interactions (Salchner et al, 2004) or social recognition memory with age (Prediger et al, 2005; Markham and Juraska, 2007). In the same line, it has been reported that older female macaques spend less time in close proximity to others and engage in fewer social interactions (Corr, 2003; Almeling et al, 2016, 2017). Together, these observations indicate that animal models can reproduce some of the age-related social cognitive deficits in humans and can help to better understand the neural correlates of such a decline.…”
Section: Introductionmentioning
confidence: 83%
“…This phenomenon has been best-studied among female-philopatric Old World monkeys, where females remain in their natal group and males disperse. For example, older rhesus macaques ( Macaca mulatta ) [25], stump-tailed macaques ( Macaca arctoides ) [26], Japanese macaques ( Macaca fuscata ) [26–30], long-tailed macaques (sometimes called crab-eating macaques; Macaca fascicularis ) [31,32] and Barbary macaques ( Macaca sylvanus ) [18,23] all exhibit reduced social engagement in terms of spatial distance to others, time spent alone, approaching others or total network size. While there has been less work examining psychological mechanisms, older rhesus macaques also show a declining propensity to follow other's gaze [19,20].…”
Section: Social Ageing Patterns Across Primatesmentioning
confidence: 99%
“…Older rhesus macaques show these changes in giving grooming and aggression even though older individuals continue to receive grooming from others at high rates, and are less likely themselves to be attacked [13,25,42,49]. Similarly, older Barbary macaques [18,23], long-tailed macaques [32], bonnet macaques [38] and Japanese macaques [24,27,29,30] also show declines in grooming given but initiate aggressive behaviours like younger adults. Macaques show similar shifts in their production of and responses to negative emotional signals or contexts: the production of negative emotional signals such as yawning and scratching increases in older adults [32]; production of conspecific threat signals generally stays consistent or increases in adult animals [42,50]; and older macaques can show exacerbated responses to external threats in controlled experiments [47].…”
Section: Social Ageing Patterns Across Primatesmentioning
confidence: 99%
See 1 more Smart Citation